THE MANIFESTATION OF GENDER INEQUALITY IN THE GIVING OF DOWRY IN THE FORM OF WHITE CLOTH/SHROUD - Susi Susilawati; Adfiyanti Fadjar; Riri Anggriani; Hayyun Nur (Universitas Negeri Semarang, 2026)
The article titled “The Manifestation of Gender Inequality in the Giving of Dowry in the Form of White Cloth/Shroud” is inspired by a social media story about a dowry consisting of a shroud and items associated with death. This incident occurred in Central Lombok, Nusa Tenggara Barat (NTB), specifically in Prapen. The news sparked lively discussions within the Ministry of Religious Affairs, particularly among heads of Religious Affairs Offices (KUA). While such an